Assessment strategies in digital learning environments: insights from teacher education institutions - Nobis, Martin Jr., L.; De Guzman, Benjielen C.; P. Cui, Alegria; Evardone, Jennifer G.; Pulga, Elena M.; Caparroso, Catherine L.; Sabalza, Lourdes Hyacinth A.; Nobis, Amabelle C. (Institute of Advanced Engineering and Science, 2025)
This study explores the adaptation of assessment strategies in teacher education programs within digital learning environments (DLEs). The perspectives and experiences of faculty members from teacher education institutions (TEIs) were analyzed using an embedded mixed-methods approach. The findings reveal significant advancements in enhancing instructor digital literacy and student engagement with DLEs. However, challenges such as the authenticity of assessments and increased student workload were identified. Faculty members recommended frequent feedback and authentic evaluations to address these issues. The study also highlights areas for improvement, including the diversification of evaluation tools, broader technology integration, and additional administrative support. These insights are crucial for TEIs to refine their assessment processes in DLE-based teacher training programs and contribute to ongoing discussions in ASEAN teacher education and global educational development.